PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR AKIDAH AKHLAK KELAS XI DI MAN 2 PONTIANAK - Fadlila Nur Hasanah; Elin B. Somantri; Mawardi Mawardi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The low mastery of students' Islamic theology and morality learning outcomes due to the dominance of passive conventional teaching models is the background of this research activity. These operational problems trigger weak internalization of spiritual values ​​and low cognitive retention of students in mastering basic daily religious concepts in class. The main focus of this scientific study is to analyze the magnitude of the effect of the application of the scramble learning model on improving the achievement of eleventh grade students' Akidah Akhlak learning outcomes. The steps of the quasi-experimental quantitative approach with a nonequivalent control group design were operated using a sample of 62 active respondents divided into control class XI C and experimental class XI E at MAN 2 Pontianak via random sampling technique. The data collection procedure was collected in a structured manner using multiple-choice tests and documentation, which were then executed through the Wilcoxon non-parametric statistical test using SPSS 27 software. Quantitative data empirically revealed an increase in the post-test results of the experimental class which reached an average of 90.03, this score was higher than the achievement of the control class which only reached 83.35. The results of the hypothesis test recorded a significance value of Asymp. Sig. (2-tailed) of 0.000, which indicates a probability of less than 0.05 so that the alternative hypothesis is accepted. The main conclusion confirms that random word reconstruction is proven to be reliable in boosting students' academic resilience. ABSTRAK Rendahnya ketuntasan hasil belajar teologi dan moralitas Islam siswa akibat dominasi model pengajaran konvensional yang pasif melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu lemahnya internalisasi nilai-nilai spiritual serta rendahnya retensi kognitif siswa dalam menguasai konsep dasar keagamaan harian di kelas. Fokus utama kajian ilmiah ini adalah menganalisis besaran pengaruh pengaplikasian model pembelajaran scramble terhadap peningkatan capaian hasil belajar Akidah Akhlak siswa kelas sebelas. Langkah-langkah pendekatan kuantitatif kuasi eksperimen dengan desain nonequivalent control group design ini dioperasikan menggunakan sampel sejumlah 62 responden aktif yang terbagi atas kelas kontrol XI C dan kelas eksperimen XI E di MAN 2 Pontianak via teknik random sampling. Prosedur pengumpulan data dihimpun secara terstruktur menggunakan tes pilihan ganda dan dokumentasi, yang selanjutnya dieksekusi melalui uji statistik non-parametrik Wilcoxon memakai bantuan perangkat lunak SPSS 27. Data kuantitatif secara empiris menyingkap peningkatan hasil post-test kelas eksperimen yang mencapai rata-rata 90,03, skor ini lebih tinggi dari pencapaian kelas kontrol yang hanya menyentuh angka 83,35. Hasil uji hipotesis mencatatkan nilai signifikansi Asymp. Sig. (2-tailed) sebesar 0,000, yang mengindikasikan probabilitas kurang dari 0,05 sehingga hipotesis alternatif diterima. Simpulan utama menegaskan bahwa rekonstruksi kata acak terbukti andal dalam mendongkrak ketahanan akademik siswa.